The adverse impact of COVID-19 on men's health. Issue 2 (March 2022) - Dubin, Justin M.; Bennett, Nelson E.; Halpern, Joshua A.
Abstract : Purpose of review: The COVID-19 pandemic has led to devastating health outcomes across the world. Initially thought to primarily affect the respiratory system, there is now clear and abundant evidence that COVID-19 can impact upon the male genitourinary system and overall men's health. In this review article, we explore the potential mechanisms by which COVID-19 specifically affects men and we review the literature examining the adverse effects of the disease on men's health Recent findings: Studies suggest that men are at higher risk for severe COVID-19 infection and death. COVID-19 infection has a negative impact on men's health including worsening semen parameters, potentially lower testosterone levels, and an increased risk of erectile dysfunction. Summary: COVID-19 is a highly pathogenic virus that exerts adverse effects upon the male genitourinary system in myriad ways. The COVID-19 infection can impact serum testosterone, fertility, sexual function, and mental health. Fortunately, the COVID-19 vaccine is safe and effective in preventing COVID-19 infection and many of these sequelae.